Dapagliflozin plus saxagliptin add‐on to metformin reduces liver fat and adipose tissue volume in patients with type 2 diabetes. Issue 7 (9th March 2020) - Johansson, Lars; Hockings, Paul D.; Johnsson, Eva; Dronamraju, Nalina; Maaske, Jill; Garcia‐Sanchez, Ricardo; Wilding, John P. H.
Abstract: Aim: To assess the effects of dapagliflozin plus saxagliptin plus metformin versus glimepiride plus metformin on liver fat (proton density fat fraction) and visceral and subcutaneous adipose tissue volumes over 52 weeks of treatment. Materials and methods: This was a magnetic resonance imaging substudy of a 52‐week, multicentre, randomized, double‐blind, parallel‐group trial that evaluated the efficacy and safety of dapagliflozin 10 mg/day plus saxagliptin 5 mg/day versus titrated glimepiride 1–6 mg (1, 2, 3, 4 or 6 mg) in 82 patients with type 2 diabetes (HbA1c 7.5%–10.5%) on metformin ≥1500 mg/day background. Analyses were exploratory and not controlled for multiplicity; P ‐values are nominal. Results: Magnetic resonance imaging was performed on 59 patients; liver fat and adipose tissue volumes were analysed for 59 and 57 patients, respectively. There was a significant >30% reduction from baseline in liver fat ( P = 0.007) and >10% reduction in adipose tissue volumes ( P < 0.01) with dapagliflozin plus saxagliptin plus metformin at week 52 versus glimepiride plus metformin. In the full‐study population, dapagliflozin plus saxagliptin plus metformin decreased body weight and serum alanine aminotransferase and aspartate aminotransferase levels over 52 weeks. Conclusions: Dapagliflozin plus saxagliptin significantly decreased liver fat and adipose tissue volume versus glimepiride, and reduced serum liver enzyme levels, indicating a favourable metabolic profile of dapagliflozin plus saxagliptin in patients with type 2 diabetes on metformin therapy.